Community Service Activities – Counseling and Anxiety Screening for Adolescents - Ernawati Ernawati; Alexander Halim Santoso; Sukmawati Tansil Tan; Yohanes Firmansyah; Agnes Marcella; Pasuarja Jeranding Ezra (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
: Counseling and screening anxiety in adolescents is an important activity in supporting adolescent mental health. Counseling activities aim to provide relevant understanding and information about anxiety in adolescents, including definitions, causes, impacts, and effective management strategies. Through interactive methods, participants are given the opportunity to share experiences and gain a better understanding of anxiety. Meanwhile, anxiety screening in adolescents aims to early detect adolescents who may experience anxiety. Using structured questions and questionnaires, mental health professionals can evaluate adolescents' anxiety levels and direct them to appropriate sources of help. Early detection of anxiety allows adolescents to get appropriate interventions and prevent further negative impacts. Counseling activities and anxiety screening in adolescents have significant benefits. Education helps reduce the stigma associated with anxiety and provides youth with the knowledge and skills to recognize and deal with anxiety in healthy ways. Anxiety screening allows teens to get help earlier and prevent anxiety from getting worse. By actively involving adolescents in counseling and screening activities, they can feel supported and gain a better understanding of anxiety. It is hoped that through these activities, youth can develop positive stress management skills, improve mental well-being, and live a more balanced and productive teenage years.